Selection the Drug Efficacy of Oroidin Derivatives as Hsp90 Inhibitors by Computer Aided Drug Design Method (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Heat shock protein 90 (Hsp90) is a conserved molecular chaperone associated with regulation of hundreds of client proteins that are key drivers, regulators and promoters of numerous refractory diseases including cancer. Consequently, Hsp90 is a significant target for the development of harmless anticancer therapies. Marine organisms are the rich source of pharmacological important compounds, especially oroidin. Oroidin, a pyrrole-2-aminoimidazole alkaloid, isolated from the marine sponge Agelas oroides, binds ATP pocket of Hsp90 and suppresses the ATPase activity of the protein. Natural product oroidin was selected as potent inhibitor of Hsp90 and its drug candidature was accordingly improved by substituting various functional groups. Virtual screenings were done through in silico studies, carried out on thirty nine derivatives of oroidin. DFT study was performed with Gaussian16, UB3LYP/6-311G++ (d, p) basis set to investigate the quantum mechanical parameters such as HOMO-LUMO energies, dipole moments. Derived parameters like ionization potential, electron affinity, softness-hardness, chemical potential and electrophilicity index were also calculated. Using AutoDock 4.0 programme, we studied docking of the thirty-nine designed derivatives with macromolecule Hsp90 and recorded the binding energy values of the best conformation out of nine in each docked compound. ADME predictions, molecular descriptor properties, and theoretical toxicity tests were evaluated using preADMET, molinspiration, and OSIRIS property explorer web tools respectively. We found twenty eight derived compounds, each docked at the same region of Hsp90, possessing higher binding energies compare to the precursor oroidin. Seven of them qualified all the rules of drug candidature and could be safe in using as effective drugs for cancer treatment. This study suggests that these compounds could be synthesized for in vitro test and may leads to a novel anticancer therapeutics.